From the perspective of traditional chinese medicine: Treatment of mental disorders in COVID-19 survivors (2020)
Purpose：The aim of this study is to explore the possible benefits of traditional Chinese medicine on the pathogenesis of psychological and mental health of COVID-19 survivors. Methods: A literature search was conducted to confirm the effects of COVID-19 on psychological and mental health of survivors. In addition to this, on the basis of signs and symptoms, TCM were used on treat mental disorder as per suggested clinical and animal experimental data plus relevant records in classical Chinese medicine books written by Zhang Zhongiing during Han Dynasty. A series of treatment plans were prescribed for COVID-19 survivors with psychological and mental disorders. Results: According to previous extensive studies focusing on effects on mental health of survivors, high incidence was observed in severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) survivors. During investigations of mental health of COVID-19 patients and survivors, it is observed that they also had symptoms of mental disorders and immune dysfunction. Furthermore, it was also proposed that depression, anxiety and post-traumatic stress disorder (PTSD) were most common mental disorders requiring special attention after the recovery from COVID-19. The symptoms of COVID-19 were analyzed, and the TCM syndrome of the depression, anxiety and PTSD after recovered from COVID19 was interpreted as internal heat and Yin deficiency. These three mental disorders pertains the category of “Lily disease”, “hysteria” and “deficient dysphoria” in TCM. Conclusion: Lily Bulb, Rhizoma Anemarrhena Decoction and Ganmai Dazao Decoction were used to treat depression. Suanzaoren Decoction, Huanglian Ejiao Decoction and Zhizi Chi Decoction were suggested for anxiety. Moreover, Lily Bulb, Rehmannia Decoction and Guilu Erxian Decoction were the formula for PTSD.